Predictors of performance in everyday technology tasks in older adults with and without mild cognitive impairment - Schmidt, Laura; Wahl, Hans-Werner (The gerontologist, 2019)
AbstractBackground and Objectives. The ability to use everyday technology has become a key competence for conducting activities of daily living, maintaining an
Published: 06 June 2018
Gesehen am 19.06.2019